2022
DOI: 10.21203/rs.3.rs-1474136/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A path-based analysis of infected cell line and COVID-19 patient transcriptome reveals novel potential targets and drugs against SARS-CoV-2

Abstract: Most transcriptomic studies of SARS-CoV-2 infection have focused on differentially expressedgenes, which do not necessarily reveal the genes mediating the transcriptomic changes. In contrast,exploiting curated biological network, our PathExt tool identifies central genes from thedifferentially active paths mediating global transcriptomic response. Here we apply PathExt tomultiple cell line infection models of SARS-CoV-2 and other viruses, as well as to COVID-19patient-derived PBMCs. The central genes mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Most hits were identified among inhibitors that target dehydrogenases, CaMK, mTOR, ULK, CLK-1, TOPK, CSF-1R, and PAK (Figure 5D). CaMK, mTOR, ULK, TOPK (also known as PBK), and PAK had already been proposed as antiviral drug targets for SARS-CoV-2 [Shahinozzaman et al, 2020; Jamaly et al, 2021; Shang et al, 2021; Agrawal et al, 2022; Basile et al, 2022]. However, we could not find any information on potential anti-SARS-CoV-2 effects caused by CLK-1 or CSF-1R inhibition.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Most hits were identified among inhibitors that target dehydrogenases, CaMK, mTOR, ULK, CLK-1, TOPK, CSF-1R, and PAK (Figure 5D). CaMK, mTOR, ULK, TOPK (also known as PBK), and PAK had already been proposed as antiviral drug targets for SARS-CoV-2 [Shahinozzaman et al, 2020; Jamaly et al, 2021; Shang et al, 2021; Agrawal et al, 2022; Basile et al, 2022]. However, we could not find any information on potential anti-SARS-CoV-2 effects caused by CLK-1 or CSF-1R inhibition.…”
Section: Resultsmentioning
confidence: 77%
“…Next, we used the caspase 3/7 activity assay in Caco-2-F03 cells to screen the Kinase Inhibitor Library (96-well)-L1200 (Selleck) for anti-SARS-CoV-2 drug candidates, which resulted in 81 hits that reduced SARS-CoV-2-induced caspase 3/7 activity by ≥ 90%. These hits included inhibitors of known potential anti-SARS-CoV-2 drug targets (CaMK, mTOR, ULK, TOPK, PAK, ROCK, CDK) [Shahinozzaman et al, 2020; Jamaly et al, 2021; Ellinger et al, 2021; Shang et al, 2021; Zhang et al, 2021b; Agrawal et al, 2022; Basile et al, 2022] and those that interfere with drug targets that had not previously been identified to be relevant during SARS-CoV-2 replication (CLK-1, CSF-1R). We determined dose response curves for 21 out of these 81 hit compounds using immunostaining for the viral S protein, which confirmed their anti-SARS-CoV-2 activities.…”
Section: Discussionmentioning
confidence: 99%
“…PBK (PDZ Binding Kinase) plays a regulatory role in cell cycle regulation and cell mitosis. It was reported that using the PathExt tool was able to identify PBK as the most common central gene target in activated TopNets to suppress SARS-CoV-2 [58]. Ekaterina et al showed that genes such as PBK regulated myofibril formation and thus caused cardiac hypertrophy [59].…”
Section: Plos Onementioning
confidence: 99%